(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In India, rapid industrialization & socio economic adjustments have caused an accelerated urban boom. However, up-gradation & implementation of the vital infrastructure has no longer kept tempo with the developing urban population. The result has been extreme pollutants of the rivers, as both untreated or partially treated sewage is being discharged into the water resources & affects the lifelines of humans of the town. At River Devika water excellent is poor for consumption and bathing requirements. Silt deposition is a fundamental issue together with the river being flooded with waste materials, excessive BOD and COD are recorded, the holy dip is sort of impossible so people are concerned about these shabby conditions. Tawi River is the main river of Udhampur city originating from Bhaderwah and walking due north to south, passing with the aid of the town Udhampur. The falling ecological health of the Tawi is a major concern nowadays. GIS is now an efficient and affordable planning information system. It is fetching an essential part of the preparation support system. The sanitation system not only deals with environmental issues but here also talks to religious advocates throughout the city, many religious activities are carried out in the Holy River Devika area. It is not at all easy to evaluate the benefits of providing a proper sanitation system and waste disposal systems in public health, the importance of which is well known.